Análisis de calidad de energía en el sistema de servicios auxiliares de las Unidades de Generación de la Central Hidroeléctrica Pucará - Velasco Sarabia, Bryan Manrique (2022)
The current research project was developed in the Pucará Hydroelectric Power Plant, with the aim to analyze the energy quality in the auxiliary services system generation units, which will allow identifying the present disturbances in the system, by problems, such as cooling pumps untimely start of the Unit 2, and light flickering of lights. The development this study is focused onto IEEE std 1159-2019 and IEEE std 519-2014 standards, what allow evaluating the set limits comply with the power quality indicators, based on the made measurements with the Fluke 435 II network analyzer. In order to validate the proposals of solutions proposed according to the made analysis, it is simulated the auxiliary services and general services system by using the Etap software. Into data analysis, it was determined: the harmonics 3, 5 and 7 presence that do not comply with the regulations limit values in the general services, and a lower 0.92 power factor in the auxiliary services in the unit 1 and in the board cooling water pump of unit 2, it has been proposed the tuned passive filters and a capacitor bank implementation has been proposed to provide a solution. By means, the study was got the energy quality indicators, further, it was made the information technical survey and the connected load characteristics to the system, by managing to identify those indicators that comply with regulations.